HAKIKAT ANAK DAN DIMENSI KEJIWAANNYA DILIHAT DARI SISI PANDANGAN ISLAM DAN PSIKOLOGI KONTEMPORER - Abdul Wahab Syakrani; Helmatun Nisa, Indah Purnama Sari, Lamdinah (CV. ADIBA AISHA AMIRA, 2025)
This study explores the nature of children and their psychological dimensions through the perspectives of Islam and contemporary psychology. In the Islamic view, children are seen as a trust from God, with rights and responsibilities that must be fulfilled by parents and society. Children are regarded as sacred beings and require nurturing to develop their fitrah. From the perspective of contemporary psychology, children are treated as individuals who develop through various stages of cognitive, social and emotional development. Contemporary psychology emphasises the importance of environmental stimulation and interpersonal relationships in shaping a child's personality and psychological well-being. An integration between these two perspectives reveals that both emphasise the importance of fulfilling children's basic needs to reach their full potential. The Islamic perspective adds a spiritual dimension that provides a moral and ethical foundation in child development, while the contemporary psychology approach offers empirical tools and methods to understand and address developmental challenges. The study concludes that a holistic approach that combines moral and spiritual values with modern scientific knowledge can provide a comprehensive framework to support children's optimal development in various dimensions of their lives.